MO202: Pulmonary-Renal Syndrome in Patient with Chronic Hepatitis C And HIV Disease. (3rd May 2022) - Šeršņova, Nadežda; Saulīte, Mikus; Kuzema, Viktorija; Petersons, Aivars
Abstract: BACKGROUND AND AIMS: Pulmonary-renal syndrome (PRS) is characterized by rapidly progressive glomerulonephritis and lung vasculitis. Most common causes of PRS are Goodpasture's disease, antineutrophil cytoplasm antibody (ANCA) associated vasculitis and systemic lupus erythematosus; rarely it could be caused by cryoglobulinemic vasculitis. ANCA and cryoglobulins are present in a wide range of infectious, inflammatory and malignant conditions with or without evidence of clinical vasculitis. ANCA positivity has been described in patients with human immunodeficiency virus (HIV) or chronic hepatitis C (HCV), but only a negligible proportion of these patients developed true ANCA vasculitis. Cryoglobulinemia is seen in ∼50% of patients with HCV and ∼5% of these patients have symptomatic disease. According to previous studies, rapidly progressive glomerulonephritis and pulmonary involvement are rare manifestations of cryoglobulinemia. We describe a patient with HIV and HCV infection who presented with rapidly progressive glomerulonephritis and lung vasculitis. METHOD: Case report presentation. RESULTS: A 43-year-old male presented with fatigue, nausea and decreased urinary output of 3–4 days. Vital signs were stable and physical examination showed abdominal distention and peripheral oedema. His past medical history included heroin abuse. However, he denied any illicit drug use, and he had been on methadone maintenance treatment for 8 years. The patient was diagnosed with HIV 11 years previously. His antiretroviral therapy included abacavir, dolutegravir and lamivudine. CD4 count before admission was 180–200 cells/mm 3 . In addition to HIV infection, the patient had HCV diagnosed 20 years ago, but he has not received any treatment. The laboratory tests revealed pancytopenia (leukocytes 1.3 × 10 9 /L, haemoglobin 66 g/L, platelets 66 × 10 9 /L), kidney injury (proteinuria 0.8 g/24 h and haematuria) with renal insufficiency (creatinine 727 mcmol/L, urea 36.6 mmol/L). Ultrasound workup demonstrated diffuse changes in liver parenchyma with signs of portal hypertension, and normal-sized, non-obstructed kidneys with Grade 0 parenchymal echogenicity. Chest CT revealed wide areas of ground-glass opacity with patchy airspace consolidations, more severe in the left upper lobe. A serologic workup was positive for cryoglobulins, ANA, c-ANCA (high titre of anti-PR3 143 IU/mL), with decreased levels of C3 and C4. CRP level was slightly elevated (40 mg/L). Moreover patient had positive treponemal and non-treponemal syphilis serological tests. An ultrasound-guided renal biopsy showed crescentic glomerulonephritis with predominant IgM and focal C3, C1q deposition in glomerular capillary walls without any significant glomerular proliferative features. Changes could be interpreted as an immune complex and/or cryoglobulin-mediated glomerulonephritis, but overlapping pauci-immune glomerulonephritis could not be ruled out. Haemodialysis was initiated due to kidney failure and hyperhydration. The patient was treated with pulse methylprednisolone followed by a tapering course of oral prednisolone. Rituximab 1000 mg was prescribed after excluding HIV opportunistic infections, and treatment of syphilis with three doses of benzathine penicillin was used. Due to low GFR, HIV treatment was switched to Dolutegravir/Rilpivirine. The patient refused to initiate HCV therapy. The patient responded well to treatment and lung vasculitis and kidney function improved, therefore haemodialysis was discontinued. Serum creatinine level decreased to 130–120 mcmol/L and remained stable after 18 weeks since the treatment. CONCLUSION: PRS in a patient with chronic infections, positive cryoglobulins and positive c-ANCA clinically seems more applicable to c-ANCA vasculitis than to cryoglobulinemic vasculitis. Still overlapping of both diseases could not be excluded.